Porifera del cañón de la Gaviera (sistemas de cañones de Avilés, mar Cantábrico). - Ríos, P.; Cristobo, J.; Sánchez, F. (Avances en estudios de biología marina: contribuciones del XVIII SIEBM GIJÓN. Temas de Oceanografía. Instituto Español de Oceanografía, Madrid. Spain, 2017)
La Gaviera Canyon is located in the Avilés Canyon System, a complex, structurally-controlled area in the Cantabrian Sea (southern Bay of Biscay), constituted by three main canyons, the La Gaviera Canyon being one of these, and some other minor tributaries. There is also a marginal platform and a relevant rocky outcrop in this area of the north Iberian continental margin.This canyon provides suitable environmental conditions for sponges and cold-water corals to grow (Sanchez et al., 2014). Its general morphology is unusual, as it is totally different from the other canyons of the Avilés Canyon System and Navia Canyon, which have clear cross-sec-tions in a V shape, while GC shows a striking U-shaped cross section. High sampling effort was performed in this area during the INDEMARES project including a complete geomorphological description, direct visual transects, experimental designs based on moorings of landers and cur-rent meter lines and samplings using dredges to determine the biodiversity associated with the reef and rocky bottoms.Porifera Biodiversity of La Gaviera Canyon is summarized and its description is updated us-ing data collected by means of rock dredge and completed by ROV Liropus 2000 and photo-grammetric sledge Politolana of the Spanish Institute of Oceanography (IEO). A total of 333 living specimens have been recorded within La Gaviera canyon in the depth range 550–1533 m. Most of them are associated with bathyal coral reefs. The scleractinian Madrepora oculataLinnaeus, 1758 and Lophelia pertusa (Linnaeus, 1758) are the main colonial species corals in the canyon and have a complex three dimensional structure providing ecological niches for a large diversity of associated species in particular sponges. Sponges use the coral structure as hard substrate and they could be assigned to different growth forms as Hollow bladder-like forms (genera Desmacella, Haliclona), thin, hispid crusts (Hymedesmia, Thrombus, Microciona, Hamacantha, Mycale), massive (Regadrella, Aphrocallistes, Phakellia, Geodia, Pachastrella) or scavating (Siphonodictyon).Porifera are clearly dominated by Class Demospongiae (93%) and two species of Class Hexactinelida (7 %): Regadrella phoenix Schmidt, 1880 and Aphrocallistes beatrix Gray, 1858.Among Demospongiae, the most abundant order is Poecilosclerida with almost a half of the collected specimens; Hymedesmia, Hamacantha and Latrunculia are the genus most abun-dant. Tetractinellida (19 %) is common taxon by the presence of genus Geodia, Calthropella, Pachastrella and Thrombus. Other orders are Halichondrida (7%), Haplosclerida (6%), Hadromerida (2 %) and Lithistida (1%) and Spirophorida (1 specimen)